Applications of CRISPR-Cas-Based Genome Editing Approaches Against Human Cytomegalovirus Infection - Andra Zhang; Isadora Zhang; Fenyong Liu (Biomedicines)
Human cytomegalovirus (HCMV), a globally ubiquitous herpesvirus with the ability to carry out both lytic productive and lifelong latent infections, is a major cause of congenital infections, often leading to intellectual disabilities and neurological disorders. Moreover, HCMV is an opportunistic pathogen commonly found in immunocompromised individuals such as organ transplant recipients, HIV-positive individuals, and cancer patients, causing severe and life-threatening complications. While effective in inhibiting viral lytic infection, current FDA-approved compounds cannot eliminate the latent viral genome and have little effect on viral latent infection. Developing novel antiviral therapeutic approaches to eliminate HCMV lytic and latent infections is a major public health priority for controlling HCMV infection and preventing viral-associated diseases. The genome-editing technology based on the Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR)/CRISPR-associated protein (Cas) RNA-guided nuclease system represents a novel and promising antiviral approach through modifying or destroying the genetic material of human viruses. This review summarizes the recently published progress in using the CRISPR-Cas approach to study and inhibit HCMV infections and discusses prospects for developing the CRISPR-based genome-editing technology for therapeutic applications against HCMV infection and associated diseases.